2018
DOI: 10.1016/j.jses.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative opioid use on outcomes after arthroscopic rotator cuff repair

Abstract: BackgroundPreoperative opioid use has been correlated to suboptimal outcomes in orthopedic surgery. This study evaluated the effect of preoperative opioid use on outcomes after arthroscopic rotator cuff repair (RCR).MethodsA retrospective review was performed of 79 patients who underwent arthroscopic RCR; of these, 31 with a history of preoperative opioid use were compared with a control group of 48 patients without a history of preoperative opioid use. Preoperative and postoperative patient-reported outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Although our findings did not show any significant difference in expectations after lumbar spine surgery in patients who took opioids compared with non-users, management of lumbar spine surgery expectations based on preoperative opioid usage should be considered in the surgeon-patient discussion before surgery [ 27 , 28 ]. Previous studies showed that pre-surgical use of opioids is a predictor of various adverse postoperative outcomes in spine surgery such as severe self-rated pain and overall health, and is associated with increased length of hospitalization, surgical complications, and delays in returning to work [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our findings did not show any significant difference in expectations after lumbar spine surgery in patients who took opioids compared with non-users, management of lumbar spine surgery expectations based on preoperative opioid usage should be considered in the surgeon-patient discussion before surgery [ 27 , 28 ]. Previous studies showed that pre-surgical use of opioids is a predictor of various adverse postoperative outcomes in spine surgery such as severe self-rated pain and overall health, and is associated with increased length of hospitalization, surgical complications, and delays in returning to work [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that pre-surgical use of opioids is a predictor of various adverse postoperative outcomes in spine surgery such as severe self-rated pain and overall health, and is associated with increased length of hospitalization, surgical complications, and delays in returning to work [ 29 ]. Moreover, opioid use before surgery is associated with a considerably higher risk of long-term opioid use and less improvement of the postoperative outcome, and preoperative pain management planning should take these observations into account [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative opioid use is associated with a higher likelihood of prolonged opioid usage and increased dose requirements after arthroscopic RCR. 5 , 24 , 30 Similarly, Sabesan et al 24 examined a cohort of 79 patients who underwent arthroscopic RCR and observed that the patients with no opioid use had significantly higher patient-reported postoperative outcomes than the patients with a history of preoperative opioid use. Patients with preoperative opioid use did not reach the same level of functionality postoperatively as patients who did not use opioids and reported higher postoperative pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with preoperative opioid use did not reach the same level of functionality postoperatively as patients who did not use opioids and reported higher postoperative pain scores. 24 , 30 In a retrospective examination of 35,155 arthroscopic RCR procedures performed over a 7-year study period, Westermann et al 29 reported that patients who filled opioid prescriptions 1 to 3 months before surgery were more likely to be filling opioid prescriptions up to 9 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that >30% of these opioid-naive patients received at least one preoperative opioid prescription, and >8% showed prolonged use, with risk factors being "greater opioid use in the early postoperative period, mental health conditions, substance dependence and abuse, and pre-existing pain disorders." Comparing arthroscopic rotator cuff repair outcome between patients with and without a history of opioid use before surgery, Sabesan et al 18 showed that both groups benefited from surgery but that the opioid-naive patients had significantly better outcome scores than the opioid-familiar group. Williams et al 19 similarly showed that opioid-familiar arthroscopic rotator cuff repair patients used almost twice the amount of postoperative opioids over almost three times the duration as did opioid-naive patients.…”
mentioning
confidence: 99%